2021
DOI: 10.1556/2006.2020.00083
|View full text |Cite
|
Sign up to set email alerts
|

“Diagnostic inflation” will not resolve taxonomical problems in the study of addictive online behaviours. •

Abstract: This article suggests that the type of Internet-enabled device should not be prioritised when conceptualizing diagnostic categories of addictive online behaviours. The diagnostic distinction between “predominantly mobile” and “predominantly non-mobile” forms of Internet use disorders (IUD) is not empirically based, may not be clinically useful and may lead to “diagnostic inflation.” Problems with the concepts of smartphone use disorder and IUD on which the proposed distinction is largely based call for their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A growing number of studies have focused on specific problematic online activities, such as online gaming disorder [ 16 ], online gambling disorder [ 17 ], Facebook addiction, [ 18 ], Instagram addiction [ 19 ], and YouTube Addiction [ 20 ], as well other specific IUDs (e.g., online pornography use disorder, online shopping disorder [ 21 ]). However, the concepts of generalized PIU and specific PIU remains debatable [ 22 ]. For instance, Griffiths has long advocated that there is a fundamental difference between addictions on the internet and addiction to the internet [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have focused on specific problematic online activities, such as online gaming disorder [ 16 ], online gambling disorder [ 17 ], Facebook addiction, [ 18 ], Instagram addiction [ 19 ], and YouTube Addiction [ 20 ], as well other specific IUDs (e.g., online pornography use disorder, online shopping disorder [ 21 ]). However, the concepts of generalized PIU and specific PIU remains debatable [ 22 ]. For instance, Griffiths has long advocated that there is a fundamental difference between addictions on the internet and addiction to the internet [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screen time known to be associated with decrease total sleep period, prolonged initiation of sleep and delayed bedtime. That was supported by many studies that long TV watching, or computers usage time was related to shorter sleep period or delayed bedtime (Zendle and Bowden-Jones 2019 ; King et al 2020 ).…”
Section: Discussionmentioning
confidence: 80%
“…Sleep quality is an indicator for health; stressed children may suffer many sleep problems depending many factors as social and family factors, his or her awareness about the problem, the extent of influence on the quality of life, more utilization of social media, acceleration of screen time using and excessive online gaming enhanced by COVID pandemic (King et al 2020 ). Sleep disorders are associated with neurocognitive and psychosocial impairments as well as an increase in caregiver burden (La Greca et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is now relative consensus that smartphone content is the primary object of problematic engagement (Elhai et al, 2019;Griffiths, 2021). Given this, it has been suggested that, like problematic internet use, PSU is an umbrella construct masking a spectrum of discrete problematic behaviours (e.g., social networking, gaming; Panova & Carbonell, 2018;Starcevic et al, 2021). However, it has also been argued that generalised PSU-that is, the excessive engagement in a range of content on a smartphone-may be a unique construct (I. H. Chen et al, 2020;Griffiths, 2021;Montag et al, 2021), an assertion supported with network analysis (Baggio et al, 2018).…”
Section: Conceptualising Problematic Smartphone Usementioning
confidence: 99%